De alimento a commodities : a produção de milho no município de Pinhão e suas contradições - Oliveira, Marina Feitosa da Rocha (2014)
The paper now presented analyzes the repercussions of maize production to the countryside and town in the municipality of Pinhão in the state of Sergipe, that despite its small land mass and population of just over 6,000 inhabitants, is gradually showing increased production this cereal, which became the flagship of municipal agricultural production and its surroundings. It is considered that Brazil is now a big producer of corn, which has grown considerably in the last ten years and estimates to predict the future expansion both in area planted as productivity. In recent years we observed in Sergipe agrarian space accelerated growth of this crop, which until then was conducted in several municipalities intercropped with other crops, but with little attention. The cereal was used to supply essentially the herds and a part for the feed and food industries. At present, it is observed that the production of corn held on a grand scale, in the mold of agribusiness, in large properties with the use of large territorial extensions to meet corn chain that supplies a network of interconnected businesses that have corn as raw base material. The hand labor employed in the cultivation of cereal has been drastically reduced, because with the intensive use of mechanization and high tech workers were replaced by machines, which perform the work of several men with more agility, which demonstrates the exclusive nature of this production, since, besides many farmers unable to compete with such high production, suppressed by the expansion of agribusiness corn and devoid of means of production to survive the land, leaving them with only their labor power to be sold were "forced" to leave their small farms in search of new ways of survival and reproduction, the few workers who still work in this production are extremely exploited and exposed to various risks, for very low wages and who undergo such a situation by the lack alternatives. The municipality of Pinion today has around it a true "green sea", the production of corn takes care of almost all arable spaces of the city, small productions of beans and other farm products are almost rarity, since besides the replacement of production the same for corn, it is difficult to survive the intensive use of herbicides and insecticides applied by air in the cornfield that damages and even exterminate small productions around. The municipal seat of Pinion, over ten years, during which there was a boom in corn production throughout the state, has shown changes in its dynamics and configuration, which may reflect the spatial distribution of corn, changes such as the installation of a bank of finance company loans, marketing inputs, fertilizers and agricultural equipment and growth of local commerce store, are changes that can be related to the "growth and development" that corn production has resulted in cities that expand the territory. However, it is important to emphasize that this development is masked by benefits, but rooted for appropriating space, monopolization of production, worker exploitation, expropriation of peasants, alienation of the population and environmental degradation, which are important aspects camouflaged by the sight of the stunning planting corn, which fills the eyes of passers-by watching and empties the dish on who planted with his own hands.